Stability of the 2p2 3Pe state of two-electron atoms near to critical nuclear charge. (14th May 2023) - Zheng, Ruo Yu; Jiao, Li Guang; Liu, Aihua; Ma, Jia; Montgomery Jr, Henry E; Ho, Yew Kam; Fritzsche, Stephan
Abstract: Critical stability of the metastable bound 2 p 2 3 P e state of two-electron atoms near the critical nuclear charge Z c (smaller than which the bound state ceases to exist) is investigated by employing the explicitly correlated Hylleraas-configuration interaction basis function. Our numerical calculation shows that, when the nuclear charge decreases to Z c, the ionization energy of the system approaches zero linearly and this behavior is fully consistent with the Hellmann–Feynman theorem. Radial and angular physical quantities as well as the inner and outer electron radial density distributions are calculated to reveal the classical geometric structure of the two-electron atom. The inner electron can be well modeled by a hydrogenic model in the 2 p state and its density distribution does not change much as the nuclear charge is changed. The outer electron, which is still localized in a finite region near the nucleus before the system transforms into a well-defined resonance, is shifted notably into a far-distance region. The critical stability of the system near the bound-continuum limit is therefore dominated by the outer electron.